2012
DOI: 10.1111/j.1526-4610.2011.02066.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Headache Before, During, and After Pregnancy: A Cohort Study

Abstract: Objective The present study endeavored to identify predictors of headache during pregnancy, shortly after delivery, and at 8-week follow-up. Background Many women suffer from headaches during pregnancy and the postpartum period. However, little is known about factors that predict headache surrounding childbirth. Methods Secondary analysis of longitudinal cohort study of 2434 parturients hospitalized for cesarean or vaginal delivery in four university hospitals in the United States and Europe. Data were gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
12
0
3
Order By: Relevance
“…MA can develop new aura symptoms during gestation [ 24 , 25 ], as pregnancy may trigger attacks of aura without headache as well [ 26 ]. In less frequent cases, hemiplegic migraine makes the differential diagnosis very difficult, especially in the third trimester [ 27 , 28 ]. Therefore, we can easily understand why transient neurologic symptoms during pregnancy are more common among pregnant women with migrainous headache than in those without headache or with non-migrainous headache [ 15 ].…”
Section: Clinical Headache Phenotypes and Observational Studies In Prmentioning
confidence: 99%
“…MA can develop new aura symptoms during gestation [ 24 , 25 ], as pregnancy may trigger attacks of aura without headache as well [ 26 ]. In less frequent cases, hemiplegic migraine makes the differential diagnosis very difficult, especially in the third trimester [ 27 , 28 ]. Therefore, we can easily understand why transient neurologic symptoms during pregnancy are more common among pregnant women with migrainous headache than in those without headache or with non-migrainous headache [ 15 ].…”
Section: Clinical Headache Phenotypes and Observational Studies In Prmentioning
confidence: 99%
“…A large longitudinal cohort study of 2434 pregnant women showed that those with a history of headache prior to pregnancy were at greater risk of experiencing headache during pregnancy [37]. There are many available treatment options for migraine during pregnancy/ lactation, so patients can be reassured that they will not suffer in pain during pregnancy.…”
Section: Therapeutic Aspectsmentioning
confidence: 99%
“…У нерожавших ГБ чаще и интенсивнее, чем у рожавших [37]. Наличие ГБ до беременности является важным предиктором ее развития во время или после беременности [38].…”
unclassified